2023
DOI: 10.1057/s41599-023-01773-0
|View full text |Cite
|
Sign up to set email alerts
|

Has the establishment of green finance reform and innovation pilot zones improved air quality? Evidence from China

Abstract: The role of finance in environmental sustainability is becoming increasingly important. This study conducts a quasi-natural experiment using a sample of 146 prefecture-level cities from 2015 to 2019. It adopts difference-in-differences to examine the impact of China’s green finance reform and innovations pilot zones (GFRIs) on urban air quality. The findings show that air quality has improved after the establishment of GFRIs, indicating that GFRIs have the potential to control air pollution levels. The mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
2
1
Order By: Relevance
“…This reveals that the government should guide and promote the development of GF to provide more financial capital for green technology and to increase the financing support for solar photovoltaic, wind, geothermal energy, and other clean renewable energy industries. However, the influence of GF on CEI and AP through IS is not significant, which is different from some results in the literature [28]. When studying the mechanism of GF's effects on CEI and AP by region (see Figure 6), it was found that the impact of GF on IS in the Eastern region is significant, which implies that the effect of GF may be affected by the level of economic development [47].…”
Section: Conclusion and Policy Recommendationscontrasting
confidence: 75%
See 1 more Smart Citation
“…This reveals that the government should guide and promote the development of GF to provide more financial capital for green technology and to increase the financing support for solar photovoltaic, wind, geothermal energy, and other clean renewable energy industries. However, the influence of GF on CEI and AP through IS is not significant, which is different from some results in the literature [28]. When studying the mechanism of GF's effects on CEI and AP by region (see Figure 6), it was found that the impact of GF on IS in the Eastern region is significant, which implies that the effect of GF may be affected by the level of economic development [47].…”
Section: Conclusion and Policy Recommendationscontrasting
confidence: 75%
“…The economic structure is usually studied in terms of both ES and IS. For example, Xu et al [28] studied the GF reform and innovation pilot zone in China and found that GF improved air quality by promoting IS optimization. Xiang et al [29] constructed a panel threshold model with IS and ES as the threshold variables, finding that the inhibitory effect of GF on AP through IS optimization is greater than that through ES optimization.…”
Section: Mechanism Of Gf's Effects On Carbon Emissions and Pollutionmentioning
confidence: 99%
“…Researcher Sivakumar A. et al [13] determined the importance of implementing innovation monitoring in health care institutions, which characterizes the assessment of the implementation of the Sustainable Development Goals in the health care sector. Researcher Xu X. et al [14] noted the need to consider green finance in the innovative activities of air carrier companies in China, which notes the high investment attractiveness of green innovation projects at the national and international levels. It should be noted that the implementation of the processes of decarbonization of production and transport by companies is relevant in the implementation of the Sustainable Development Goals, the scientist A. Raihan [15] studied the contribution of economic development, renewable energy sources, technical progress and forestry by Uruguayan companies with the aim of becoming a carbon-neutral country by 2030 year.…”
Section: Literature Reviewmentioning
confidence: 99%